Form as a Driver for Regeneration: A Methodological Approach to Rethinking School Building Infrastructure in Italy - Caterina Barioglio; Daniele Campobenedetto; Lorenzo Murru; Caterina Quaglio (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Italian school infrastructure is a multi-layered and diversified spatial asset which requires systemic rethinking in order to respond to evolving educational, energy and health needs. This has become evident not only as a consequence of the Covid-19 emergency, but also due to demographic and educational changes that have taken place over the years. The objective of the present work is to outline a methodological approach aimed at promoting agency within local communities and defining regeneration priorities and strategies through the co-construction of shared spatial knowledge. In a context in which tools and funds for a substantial renovation of the Italian public infrastructure are and will be available, the article explores the theoretical framework that enabled the implementation of a specific design tool — a web application — as a replicable operative model for school regeneration and describes how its prototype was built. More precisely, the web app is aimed at supporting and empowering the actors entrusted with governing the transformation of schools by identifying spatial resources and potentials. To this end, typological classification based on the current spatial characteristics of the buildings is assumed as a way to highlight the transformation potential of schools and to outline intervention priorities at a regional level. Drawing on the concept of spatial agency, the physical space of schools is therefore conceived as a shared documentary basis for the development of multi-scalar governance systems.